Quingua mga salaysay na may kasaysayan tungkol sa Plaridel, Bulacan - Veneracion, Jaime B.; National Commission on Culture and the Arts (Philippines) ([Bulacan] Jaime B. Veneracion, 2013)
History of Plaridel, a town in Bulacan Province, Philippines.
With author's dedication and signature--Title page.
"Published by the author through a grant from the National Commission on Culture and the Arts."--Title page verso.
Includes bibliographical references (pages 243-246) and index.
UCWS-3347g donated by NCCA.
Keywords: Plaridel (Bulacan Province, Philippines) -- History